Clinical Outcomes of Oleander Seed Poisoning Based on Biochemical and Cardiac Parameters (Journal of Pharmaceutical Negative Results, 2023)
Background: Oleander seed poisoning is common in Villupuram district of Tamil Nadu, India, and its neighbouring districts.Objectives: To assess the clinical outcomes of oleander seed poisoning based on biochemical and cardiac parameters. We also analysed the clinical course of patients with oleander seed poisoning with reference to clinical profile, ECG changes, echocardiographic changes, and electrolytic changes.Methods: This was a single centre nonrandomized prospective observational study conducted in the Department of General Medicine, Government Villupuram Medical College, Villupuram, Tamil Nadu, India between November 2019, and December 2021. The study included hundred consecutive patients (18 to 60 years of age and admitted within 24 hours of consumption) of oleander seed poisoning. The patients were followed up with electrocardiography, echocardiography, and specified laboratory investigations.Results: Majority (96.0%) of the patients had complete recovery, whereas two patients were referred to higher institution and two patients died. Nearly half (48.0%) the patients developed cardiotoxicity following Oleander seed consumption (34.0% had mild and 14.0% had severe cardiotoxicity). The highest incidence of cardiotoxicity was on day 1 and 2. The most common abnormal findings were bradycardia (40.0%); 10.0% patients had SA nodal exit block and 30.0% had sinus bradycardia. Cardiotoxicity was higher among patients consuming yellow Oleander seeds (95.8%), crushing the seeds before swallowing (87.8%), consumption in empty stomach (60.9%), not given first aid (64.3%), and among patients presenting to hospital beyond five hours of consuming Oleander seeds (71.4%). Patient outcome (recovery or death or referral) correlated with the number of seeds consumed. It was found that 75.0% of those who consumed more than five seeds developed severe cardiotoxicity. More than half (54.0%) the patients had GI manifestations; vomiting was the commonest symptom reported by 41.0%. The most common non-GI symptom reported was giddiness (37.0%). In echocardiography, 7 patients had features suggestive of toxic myocarditis including global hypokinesia and decreased LV systolic function.Conclusion: Oleander seed poisoning is a significant healthcare concern in rural south India. Cardiotoxicity is the prominent feature of Oleander seed poisoning. It is the need of the hour to explore the sociological and psychiatric aspects of oleander seed poisoning. Alongside, better, early diagnostic facilities and medical treatments (overall, a holistic strategy) should be developed.